Analysis of Industry Potential in Improving the Welfare of Coconut Shell Charcoal Craftsmen in Jember Regency - Farid Wahyudi; Ahmad Sauqi; Jamaliyah Putri Agustina (ABM: International Journal of Administration, Business and Management, 2025)
Industry refers to activities that process raw materials or semi-finished goods into products with added value, with the aim of generating profit. Coconut shell charcoal is a type of charcoal made from coconut shells that are burned through an incomplete combustion process. The increasing demand for this type of charcoal must also be balanced with the availability of coconut shells. Although this industry faces various challenges such as raw material supply, production techniques, labor, management, and marketing, it remains viable. The objectives of this research are: (1) To identify the development potential of the coconut shell charcoal industry in improving the welfare of craftsmen in Jember Regency. The research method used is descriptive qualitative with a phenomenological study approach. Data analysis techniques employed the assistance of the Nvivo 12 Pro application through four stages: data import, data coding, data visualization, and data extraction. Sampling techniques used purposive sampling and snowball sampling, involving a total of 6 informants. The results of this study indicate that with the availability of raw materials, high market demand, and favorable opportunities, the coconut shell charcoal industry has the potential to remain sustainable and contribute to the economic improvement of craftsmen, particularly in enhancing their welfare